Pain medicine an interdisciplinary case-based approach - Hayek, Salim M.; Shah, Binit J.; Desai, Mehul J.; Chelimsky, Thomas C. (Oxford University Press, 2015)
Pain Medicine approaches the management of common chronic pain conditions using a unique interdisciplinary approach focusing on multiple facets of patients' clinical presentations.